Fabrication of double-metal waveguide Terahertz semiconductor lasers - Wong, Gavin Kai Wen (Nanyang Technological University, 2023)
Terahertz technology has shown great promise to be used in many different fields. Terahertz Quantum cascade laser has shown to have great potential as a terahertz radiation source. In this paper, we will explore the fabrication process of double-metal waveguide structure Terahertz (~50-300um) quantum cascade lasers and try to improve their performance through the optimized processing and using novel metal waveguide materials, such as Ag instead of Au. After the fabrication process, we will characterise the fabricated device using a Fourier transform infrared spectroscope the observe the lasing properties of the new device.